Relationship building : Hair beauty salons and their customers - Tudin , Rabaah; Tambabaki , Ellen (Universiti Malaysia Sarawak (UNIMAS), 2012)
The aim of this research was to investigate how service providers (Hair Beauty Salons) turn walk-in customers into loyal consumers and if service providers’ age influences their approaches in enhancing relationship with their consumers. Data was gathered through in-depth interview with thirty (30) salon owners or their representatives in Kuching City, Sarawak.